The Ouw Natural Clay Impregnation Using Titanium Dioxide as a Rhodamine B Dyestuff Degrader - Bijang, Catherina M.; Nurdin, M.; Latupeirissa, Jolantje; Aziz, Thamrin; Talapessy, Firda (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
This study aims to determine the effect of calcination temperature on Titanium dioxide impregnated Ouw Natural Clay (LAO) on the degradation of Rhodamine B dye. The calcination temperature used was 200, 300, and 400 °C. Their radiation was carried out with 3x8 watt UV lamps and sunlight. The degradation percentage of Rhodamine B dye produced by LAO-TiO2 calcined at a temperature of 200, 300, and 400 °C with sunlight were 98.80%, 98.87%, and 96.07%, respectively. The degradation percentage of Rhodamine B dye produced by LAO-TiO2 calcined at temperatures of 200, 300, and 400 °C with the help of UV light were 96.01%, 97.41 %, and 97.18%, respectively.